Luring (The Making of Riley Paige-Book 3) - Blake, Pierce (Lukeman Literary, 2019)
"A masterpiece of thriller and mystery! The author did a magnificent job developing characters with a psychological side that is so well described that we feel inside their minds, follow their fears and cheer for their success. The plot is very intelligent and will keep you entertained throughout the book. Full of twists, this book will keep you awake until the turn of the last page." --Books and Movie Reviews, Roberto Mattos (re Once Gone) LURING (The Making of Riley Paige-Book Three) is book #3 in a new psychological thriller series by #1 bestselling author Blake Pierce, whose free bestseller Once Gone (Book #1) has received over 1,000 five star reviews. A serial killer is using barbed wire to kill a series of women, and the FBI, at a loss, must break protocol and turn to its brilliant 22 year old academy recruit, Riley Paige, to solve the case. Riley Paige is accepted into the grueling FBI academy, and is determined to finally keep a low profile and work hard with her peers. But that is not meant to be, as she is hand-picked to help her mentors to profile and hunt down a serial killer that has terrified the nation. What sort of diabolical killer, Riley wonders, would use barbed wire to kill his victims? There is no time for Riley to make a mistake in this deadly game of cat and mouse, with her own future on the line, and with a killer out there that may just be smarter than her. An action-packed thriller with heart-pounding suspense, LURING is book #3 in a riveting new series that will leave you turning pages late into the night. It takes readers back 20 plus years-to how Riley's career began-and is the perfect complement to the ONCE GONE series (A Riley Paige Mystery), which includes 14 books and counting. Book #4 in THE MAKING OF RILEY PAIGE series will be available soon.
Keywords: Krimi, detektivky